2013
DOI: 10.5194/acp-13-579-2013
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated variations of O<sub>3</sub>, CO and deep convection in the tropical/subtropical upper troposphere observed by the Aura Microwave Limb Sounder (MLS) during 2004–2011

Abstract: Abstract. The interrelated geographic and temporal variability seen in more than seven years of tropical and subtropical upper tropospheric (215 hPa) ozone, carbon monoxide and cloud ice water content (IWC) observations by the Aura Microwave Limb Sounder (MLS) are presented. Observed ozone abundances and their variability (geographic and temporal) agree to within 10-15 ppbv with records from sonde observations. MLS complements these (and other) observations with global coverage and simultaneous measurements of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 80 publications
(94 reference statements)
4
41
0
Order By: Relevance
“…We ignore any measurements which may have been influenced by clouds through the recommended screening processes using the MLS data quality flags. Comparisons between MLS O 3 and ozonesondes show the best agreement (better than 10%) in the tropical upper troposphere at 215 hPa with small positive biases (<10 ppb over the Pacific) but indicate larger biases at other pressure levels [Livesey et al, 2012].…”
Section: Datamentioning
confidence: 90%
“…We ignore any measurements which may have been influenced by clouds through the recommended screening processes using the MLS data quality flags. Comparisons between MLS O 3 and ozonesondes show the best agreement (better than 10%) in the tropical upper troposphere at 215 hPa with small positive biases (<10 ppb over the Pacific) but indicate larger biases at other pressure levels [Livesey et al, 2012].…”
Section: Datamentioning
confidence: 90%
“…Froidevaux et al (2008) compared the previous v2.2 MLS ozone retrievals with matching ozone data from ground-based and satellite observations and found that the differences are generally within 5 % in most of the stratosphere, although residuals of 10-20 % were found in the lower stratosphere. Livesey et al (2013) reports differences between the v3.3 and v2.2 MLS ozone profiles typically within 1-2 % in the stratosphere and lower mesosphere.…”
Section: Comparisons With Independent Datamentioning
confidence: 96%
“…2d), both CO emission and IWC anomalies are significantly correlated with UT CO anomaly (0.77 and −0.66, respectively), suggesting that both CO emission and convective transport are important in determining the interannual variation of UT CO over this region. The negative correlation between UT CO and IWC anomalies over this region is expected from the decrease of convection and increase of CO emission related to the intense drought-induced fires (e.g., Liu et al, 2013;Livesey et al, 2013). …”
Section: Regions Affecting Ut Co Interannual Variationmentioning
confidence: 99%
“…Duncan and Logan (2008) analyzed the factors that regulate the trends and interannual variability of tropospheric CO for 1988-1997 through a model study, and found the interannual variation of biomass burning, especially those major burning events in Indonesia associated with El Niño, is the main driver of large-scale CO variability in the tropics. Strong interannual variation of CO in the upper troposphere (UT) is found to be mainly related to the intense droughtinduced fires in Indonesia and South America (Liu et al, 2013;Livesey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%